Unraveling cancer progression pathways and phytochemical therapeutic strategies for its management - Sharma, Vikas; Chaudhary, Anis Ahmad; Bawari, Sweta; Gupta, Saurabh; Mishra, Richa; Khan, Salah-Ud-Din; Ali, Mohamed A. M.; Shahid, Mohammad; Srivastava, Saurabh; Verma, Devvrat; Gupta, Arti; Kumar, Sanjay; et al. (Frontiers in Pharmacology, 2024)
Cancer prevention is currently envisioned as a molecular-based approach to prevent carcinogenesis in pre-cancerous stages, i.e., dysplasia and carcinoma in situ. Cancer is the second-leading cause of mortality worldwide, and a more than 61% increase is expected by 2040. A detailed exploration of cancer progression pathways, including the NF-kβ signaling pathway, Wnt-B catenin signaling pathway, JAK-STAT pathway, TNF-α-mediated pathway, MAPK/mTOR pathway, and apoptotic and angiogenic pathways and effector molecules involved in cancer development, has been discussed in the manuscript. Critical evaluation of these effector molecules through molecular approaches using phytomolecules can intersect cancer formation and its metastasis. Manipulation of effector molecules like NF-kβ, SOCS, β-catenin, BAX, BAK, VEGF, STAT, Bcl2, p53, caspases, and CDKs has played an important role in inhibiting tumor growth and its spread. Plant-derived secondary metabolites obtained from natural sources have been extensively studied for their cancer-preventing potential in the last few decades. Eugenol, anethole, capsaicin, sanguinarine, EGCG, 6-gingerol, and resveratrol are some examples of such interesting lead molecules and are mentioned in the manuscript. This work is an attempt to put forward a comprehensive approach to understanding cancer progression pathways and their management using effector herbal molecules. The role of different plant metabolites and their chronic toxicity profiling in modulating cancer development pathways has also been highlighted.